'Making It Mine': An interview with comics creator Dan McDaid. Issue 1 (1st July 2016) - Gangnes, Madeline B.
Dan McDaid is a comics artist and writer who currently lives in Dundee, Scotland. He has worked on projects for Doctor Who Magazine, Dark Horse Comics, Image Comics, DC Comics, BOOM! Studios, and IDW, among others. His most recent projects are Dawn of the Planet of the Apes for BOOM! Studios and Judge Dredd: Mega-City Zero for IDW. I spoke with Dan in Dundee on 28 November 2014 to discuss his career, his artistic and writing influences, and his creative process.